The Level of E-commerce Implementation and SMEs Performance in Ibadan city Nigeria - Ayokunmi, Lawal Abideen; Rashid, Umi Kartini (Research in Management of Technology and Business, 2022)
The performance of SMEs is inextricably linked to the strengthening and enhancement of Nigeria's development.  However, some Nigerian SMEs perform poorly as a result of futile e-commerce implementation. The purpose of this paper is to investigate the level of e-commerce implementation and SMEs performance of small and medium-sized enterprises (SMEs) in Ibadan city, Nigeria. The data was collected from owners/managers of 370 SMEs in Ibadan using structured questionnaires sent via mail. The questionnaire data were analyzed using the Statistical Package for Social Science (SPSS). The findings revealed that the level of e-commerce implementation and SMEs performances in Ibadan city, Nigeria were at good level. SMEs' owners/managers were aware of the benefits of e-commerce implementation and effectively implemented the various practices to improve their performance. As a result, the study recommended that the government provide support and guidance to these SMEs in utilizing and implementing e-commerce practices by improving the level of e-commerce implementation of SMEs in the country, keeping them abreast of the latest technology as it relates to their businesses, sharpening their information retrieval skills, business development skills, security issues, use and applications of various e-commerce implementation practices, among other things.